THE IMPLEMENTATION OF SCHOOL BASED ENGLISH CURRICULUM IN ELEMENTARY SCHOOL LEVEL (A CASE STUDY AT SDN KEBUN BUNGA 06 BANJARMASIN) - Rahayu, Puji Sri (English Department of Faculty of Tarbiyah and Teacher Training, 2013)
This research is conducted to find out the implementation of SBC in English teaching in elementary school and also the challenges faced by the teachers in Banjarmasin South Kalimantan. Questionnaire, observation, interview, and documentation were used to gather the data .The data needed are the implementation of SBC in English teaching which can be seen from the syllabus, lesson plan used by teachers and the implementation in class and also the challenges that the teachers face in implementing it. The result showed that SDN Kebun Bungan has already implemented the It can be seen from the preparation, practice and evaluation The challenges faced by English teacher here are diversity of students and limited time allocation for English